IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Norjihan Md Salleh - Md Salleh, Norjihan (2015)
Article on: Article 1 - “Digital preservation of audio, video and ﬁlm” Article 2 - “The public-private partnership case study in digitization of audiovisual heritage”